(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
According to many researchers, the lack of spatial thinking skills among students persists from school even until they graduate from university. In addition, the experience of teachers of secondary and higher educational institutions and psychologists, educational researchers shows that students are not able to solve problems based on logical and spatial thinking. All this indicates that in secondary schools, although due attention is not paid to the development of spatial thinking, more educational work is carried out aimed at expanding verbal and logical thinking.